2015
DOI: 10.1038/srep16328
|View full text |Cite
|
Sign up to set email alerts
|

Global effects of agriculture on fluvial dissolved organic matter

Abstract: Agricultural land covers approximately 40% of Earth’s land surface and affects hydromorphological, biogeochemical and ecological characteristics of fluvial networks. In the northern temperate region, agriculture also strongly affects the amount and molecular composition of dissolved organic matter (DOM), which constitutes the main vector of carbon transport from soils to fluvial networks and to the sea, and is involved in a large variety of biogeochemical processes. Here, we provide first evidence about the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
50
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 26 publications
(56 reference statements)
6
50
1
3
Order By: Relevance
“…Therefore, studies are urgently needed to better understand how anthropogenic activities impact the amount and composition of dissolved OM (DOM) mobilized from terrestrial ecosystems into aquatic networks. Previous studies have shown that mobilization of aged dissolved organic carbon (DOC) is positively correlated with human disturbance worldwide (Butman et al, ) and that anthropogenic pressures such as land cover change impact DOM composition (Graeber et al, ; Heinz et al, ; Wilson & Xenopoulos, ). This is fundamentally important as DOM composition controls its photoreactivity, bioavailability, and ultimately its persistence in the environment (D'Andrilli et al, ; Kellerman et al, ; Lu et al, ; Maizel et al, ; Marschner & Kalbitz, ; Spencer et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies are urgently needed to better understand how anthropogenic activities impact the amount and composition of dissolved OM (DOM) mobilized from terrestrial ecosystems into aquatic networks. Previous studies have shown that mobilization of aged dissolved organic carbon (DOC) is positively correlated with human disturbance worldwide (Butman et al, ) and that anthropogenic pressures such as land cover change impact DOM composition (Graeber et al, ; Heinz et al, ; Wilson & Xenopoulos, ). This is fundamentally important as DOM composition controls its photoreactivity, bioavailability, and ultimately its persistence in the environment (D'Andrilli et al, ; Kellerman et al, ; Lu et al, ; Maizel et al, ; Marschner & Kalbitz, ; Spencer et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Increased water residence time and water transparency due to impoundments can lead to low CO 2 levels related to enhanced primary production . Agriculture can enhance mobilisation of labile soil organic matter (Wilson and Xenopoulos, 2009;Graeber et al, 2012Graeber et al, , 2015Lambert et al, 2017) and potentially enhance organic matter degradation and the production of CO 2 and CH 4 in rivers, although this has been seldom investigated (Bodmer et al, 2016). Leaching of nitrogen from artificial fertilizers from agricultural soils leads to enhanced in-stream N 2 O production, presumably related to enhanced denitrification (Beaulieu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A further intensification of agriculture in tropical developing countries is expected since, in addition to population growth, food demand per capita will increase with the increase in gross domestic product in the future (Graeber et al, 2015). Thus, intensification of agriculture may result in the release of large quantities of biogeochemically reactive DOM to river networks, altering the DOM-related biogeochemical cycles, and increasing the productivity, respiration, and depletion of CO 2 from river networks (Graeber et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The biogeochemical characterization of the dissolved organic matter (DOM) based on fluorescence allows the detection of differences between natural and anthropogenic DOM sources in rivers impacted by agricultural residues ; (Wilson e Xenopoulos, 2008). A combination of optical properties (fluorescence and absorption), coupled with conventional DOC measurements, can be used to understand how changes and intensification in agricultural land use can modify the quantity and composition of DOM (Graeber et al, 2015).…”
Section: Introductionmentioning
confidence: 99%